Swearing on Twitter: Khaleeji Dialect - Al-Qattan, Abdullah (European Scientific Journal, ESJ, 2021)
Swearing is an inevitable part of any language and culture around the world, yet each culture has its own distinctive swear words and phrases used among its members. This language phenomenon is observed on Twitter, one of the most popular social network platforms where heated comments often occur. In this study, the examination of the Khaleeji dialect of the Arabian Gulf countries on Twitter reflects the influence of culture, religion, and language on the perception and use of swearing in the Arabian Gulf. Upon corpus-based categorization and analysis of one hundred swear words and phrases written by Khaleejis on Twitter, the data shows that Khaleejis refer to ten different thematic swearing categories, with animals being their top reference. The findings accordingly answer the following questions: What swear words do Khaleejis often use? What is the logic behind opting for the swear words recorded?